Escherichia coli and Salmonella sp. On Fishery Frozen Products at the Fish Quarantine, Quality Control, and Fisheries Product Safety Center Surabaya II, East Java - Santika Dwi Christanti (Airlangga University, 2019)
Frozen fishery products are a type of commodity with varying levels of development, both in whole and in the form of pieces. Fishery products are foodstuffs that are very easily contaminated with pathogenic microbes that can cause food poisoning and cause disease outbreaks in consumers. This study aims to find out the different types of pathogenic bacteria that contaminate fishery frozen products. The fishery frozen products studied came from tuna, mackerel, mollusks and crustaceans. Examination of Escherichia coli bacteria using the METHOD ISO 16649-3:2015 and Salmonella sp bacteria. It uses iso 6579:2002. The results of tests that have been done can be known that frozen fishery products there are positively contaminated and negative contaminated with Escherichia coli and Salmonella sp.